LINGUISTIC INTERFERENCE AS A PSYCHOLINGUISTIC AND SOCIOLINGUISTIC PHENOMENON (Conferencea, 2022)
Learning a new language is always challenging, there are some factors that can affect the learning process. In this case, the role of native language is also essential and language interference may occur in learning a second or a foreign language. Therefore, linguistic interference should be learned from the psycholinguistic and sociolinguistic aspects.